Electronic Medical Record Documentation of Driving Safety for Veterans with Diagnosed Dementia. Issue 1 (1st January 2018) - Vair, Christina L.; King, Paul R.; Gass, Julie; Eaker, April; Kusche, Anna; Wray, Laura O.
ABSTRACT: Objectives : Many older adults continue to drive following dementia diagnosis, with medical providers increasingly likely to be involved in addressing such safety concerns. This study examined electronic medical record (EMR) documentation of driving safety for veterans with dementia ( N = 118) seen in Veterans Affairs primary care and interdisciplinary geriatrics clinics in one geographic region over a 10-year period. Methods : Qualitative directed content analysis of retrospective EMR data. Results : Assessment of known risk factors or subjective concerns for unsafe driving were documented in fewer than half of observed cases; specific recommendations for driving safety were evident for a minority of patients, with formal driving evaluation the most frequently documented recommendation by providers. Conclusion : Utilizing data from actual clinical encounters provides a unique snapshot of how driving risk and safety concerns are addressed for veterans with dementia. This information provides a meaningful frame of reference for understanding potential strengths and possible gaps in how this important topic area is being addressed in the course of clinical care. Clinical Implications : The EMR is an important forum for interprofessional communication, with documentation of driving risk and safety concerns an essential element for continuity of care and ensuring consistency of information delivered to patients and caregivers.